Olfactory disorder in Parkinson's disease - REN Peng, CHEN Yali, ZHANG Xianwen (Jichu yixue yu linchuang, 2023)
Olfactory dysfunction is the most common early non-motor symptom of Parkinson's disease (PD), which is used as a marker for the diagnosis of PD. The mechanism of olfactory dysfunction is very complex, which is a challenge in the research. The neuromediator such as the accumulation of α-synuclein, dopamine (DA), acetylcholine (ACh), 5-hydroxytryptamine (5-HT) and inflammatory factors are implicated in the olfactory dysfunction in PD. To further study the mechanism of olfactory dysfunction in PD may provide new ideas and therapeutic targets for treatment.